Controlled air exchange rate method to evaluate reduction of volatile organic compounds by indoor air cleaners. (February 2023) - Rajapakse, Maneeshin Y.; Pistochini, Theresa E.; Borras, Eva; McCartney, Mitchell M.; Davis, Cristina E.
Abstract: Air cleaning technologies are needed to reduce indoor concentrations and exposure to volatile organic compounds (VOCs). Currently, air cleaning technologies lack an accepted test standard to evaluate their VOC removal performance. A protocol to evaluate the VOC removal performance of air cleaning devices was developed and piloted with two devices. This method injects a VOC mixture and carbon dioxide into a test chamber, supplies outdoor air at a standard building ventilation rate, periodically measures the VOC concentrations in the chamber using solid phase microextraction-gas chromatography-mass spectrometry over a 3-h decay period, and compares the decay rate of VOCs to carbon dioxide to measure the VOC removal air cleaning performance. The method was demonstrated with both a hydroxyl radical generator and an activated carbon air cleaner. It was shown that the activated carbon air cleaner device tested had a clean air delivery rate an order of magnitude greater than the hydroxyl radical generator device (72.10 vs 6.32 m 3 /h). Graphical abstract: Image 1 Highlights: Method to evaluate air cleaner volatile organic compound removal performance. Clean air delivery rate for removal of volatile organic compounds. CADR of carbon filter was eleven times the hydroxyl radical generator tested.